Peran Motivasi, Budaya Organisasi, Pengembangan Karir dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. Indomarco Adi Prima Semarang - Irfan Akbar Maulana; Efriyani Sumastuti; Noni Setyorini (Lembaga Pengembangan Kinerja Dosen, 2026)
Employee performance is a crucial factor in supporting a company's success, particularly in the face of increasingly fierce business competition. PT. Indomarco Adi Prima Semarang is required to manage its human resources effectively to enable employees to achieve organizational targets and goals. Factors suspected of influencing employee performance include work motivation, organizational culture, career development, and organizational commitment. The discrepancies in previous research regarding the influence of these variables prompted this study. This study aims to analyze the influence of motivation, organizational culture, career development, and organizational commitment on employee performance at PT. Indomarco Adi Prima Semarang, both partially and simultaneously. The method used was quantitative research, with data collected through questionnaires and analysis using multiple linear regression. The results showed that motivation had no effect on employee performance, organizational culture had no effect on employee performance, career development had a significant effect on employee performance, and organizational commitment had a tendency to have an effect but was not strong enough to be declared significant at the 5% level. These findings indicate that career development is the most dominant factor in improving employee performance at PT. Indomarco Adi Prima Semarang.